MAPK4 inhibits the early aberrant activation of B cells in rheumatoid arthritis by promoting the IRF4-SHIP1 signaling pathway - Pei Huang; Guangli Yang; Pingping Zhang; Yin Zhu; Yaning Guan; Jian Sun; Qian Li; Yang An; Xiaoqi Shi; Juanjuan Zhao; Chaohong Liu; Zhixu He; et al. (Cell Death and Disease)
Abstract The involvement of B lymphocytes in the pathogenesis of rheumatoid arthritis (RA) is well-established, with their early and aberrant activation being a crucial factor. However, the mechanisms underlying this abnormal activation in RA remain incompletely understood. In this study, we identified a significant reduction in MAPK4 expression in both RA patients and collagen-induced arthritis (CIA) mouse models, which correlates with disrupted B cell activation. Using MAPK4 knockout (KO) mice, we demonstrated that MAPK4 intrinsically promotes the differentiation of marginal zone (MZ) B cells. Loss of MAPK4 in KO mice enhances proximal BCR signaling and activates the PI3K-AKT-mTOR pathway, leading to heightened B cell proliferation. Notably, B cells from MAPK4 KO mice produce significantly higher levels of IL-6, a key pro-inflammatory cytokine in RA. Furthermore, MAPK4 KO mice exhibit impaired T cell-independent humoral immune responses. Mechanistically, MAPK4 inhibits the activation of the PI3K signaling pathway in B cells by activating the IRF4-SHIP1 pathway. Treatment with the MAPK4 agonist Vacquinol-1 enhances MZ B cell differentiation in WT mice and reduces IL-6 secretion in CIA mouse models. In summary, this study reveals the diverse roles of MAPK4 in regulating of B cell functions, with potential implications for developing therapeutic strategies for RA and related autoimmune diseases.